Elite política y partidos políticos en Cali de 1958 a 1998 - Sáenz, José Darío (Sociedad y Economía, 2005)
The character of the members of the political elite in Cali has changedsubstantially over the past 40 years: there has been a transition from an elite ofeconomic power that was the self-appointed representative in the in the spheresof local political decisions to a professional political elite, that lives of and forpolitics, which is the main feature of the modern forms of political dominance.The Conservative and Liberal parties, with only minor differences among them,have become the salient instances of recognition and legitimity for the local political elite, due to the fact that they mantain the key elements of the economic project of such an elite, and sustain the functioning of the electoral petty organizations created by its members.